PENGEMBANGAN APLIKASI WEB UNTUK MANAJEMEN LAYANAN KESEHATAN (E-HEALTH SYSTEM) - Ninda Pradana; Kausar Rusdin; Zulfikar Isnansah; Arman Rusdin; Dhimas Tribuana; Dayanti Dayanti (Jurnal Teknologi dan Bisnis Cerdas, 2026)
Digital transformation has driven healthcare systems to shift from conventional service models toward more integrated, efficient, and accessible care delivered through web-based e-health platforms. Web-based e-health applications have become the backbone of this transformation by offering innovative solutions to improve service quality, medical data accuracy, and patient satisfaction. This study aims to systematically map the technological architectures, functional features, implementation challenges, and impacts of web application development for healthcare service management (E-Health Systems) through a Systematic Literature Review (SLR) approach. The research method employed a systematic review of 20 scholarly articles published between 2020 and 2025, retrieved from reputable databases including IEEE Xplore, ScienceDirect, Scopus, and Google Scholar, based on clearly defined inclusion and exclusion criteria. The synthesis results indicate that modern architectures based on React.js, Node.js, microservices, and cloud computing are widely adopted to support intelligent Electronic Medical Records (EMR), integrated telemedicine ecosystems, and healthcare data analytics modules. The most frequently implemented features include web-based EMR, comprehensive telemedicine services, and data analytics platforms for clinical decision support. However, several key challenges remain, particularly advanced cybersecurity risks, interoperability gaps despite the adoption of standards such as FHIR, and socio-technical barriers affecting system acceptance and utilization by healthcare professionals and patients. These findings emphasize that the successful implementation of web-based e-health applications depends heavily on the integration of reliable technologies, user-centered interface design, and ethical data governance to ensure secure, inclusive, and patient-centered healthcare services.